Reporting of Ethical Considerations Associated with Clinical Trials Published in Iranian Dental Journals between 2001 and 2011. - Nader Navabi; Arash Shahravan; Ali Modaberi (Tehran University of Medical Sciences, 2013)
Ethical consideration is a basic requirement for design of randomized clinical trials. The purpose of this study was to assess whether reports of Iranian dental clinical trials complied with the requirements of the ethical principles of human research.In this retrospective observational study electronic search was performed to identify all dental clinical trials published between 2001 and 2011. Each trial report was assessed for inclusion of a statement that 17 items about research ethics.Totally 242 papers were identified, of which 15.3%, stated that ethical approval had been obtained and 50.4% of the trial reports indicated that informed consent had been obtained. The mean ethical score for the mentioned studies was 7/68 out of 17.Most Iranian dental clinical trial reports failed to consider important ethical principles. The reporting of the ethical issues associated with these trials could be improved further not only by the instructions to authors, but also by Journal editors refusing to publish trials that do not comply.